2021
DOI: 10.1080/10717544.2021.2021325
|View full text |Cite
|
Sign up to set email alerts
|

A pH-responsive complex based on supramolecular organic framework for drug-resistant breast cancer therapy

Abstract: Chemotherapy is one of the main ways to treat breast cancer clinically. However, the multidrug resistance to anti-tumor drugs limits their clinical use. To overcome these drawbacks, development of drug delivery systems (DDSs) has attracted more and more attention in cancer therapy. At present, the preparation and purification process are complicated for many reported DDSs, while clinic calls for new DDSs that are more convenient for preparation. Here, a new pH-responsive supramolecular organic framework drug d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We thus prepared hydrazone derivative T2 (Chart 1) to test this possibility because the acid-responsive hydrolysis of hydrazone has been widely used for the design of drug delivery systems and prodrugs. 49 Its 1:2 mixture with CB [8] led to the formation of dSOF2, 32 which has an aperture of 2.7 nm. Both in vitro and in vivo experiments showed that dSOF2 could also include doxorubicin and enhance its activity against MCF-7/ADR cells and tumors through intracellular delivery.…”
Section: Sofs As In-situ Loading Carriers For Drug and Dna Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…We thus prepared hydrazone derivative T2 (Chart 1) to test this possibility because the acid-responsive hydrolysis of hydrazone has been widely used for the design of drug delivery systems and prodrugs. 49 Its 1:2 mixture with CB [8] led to the formation of dSOF2, 32 which has an aperture of 2.7 nm. Both in vitro and in vivo experiments showed that dSOF2 could also include doxorubicin and enhance its activity against MCF-7/ADR cells and tumors through intracellular delivery.…”
Section: Sofs As In-situ Loading Carriers For Drug and Dna Deliverymentioning
confidence: 99%
“…dSOF1a – h were prepared in boiling water at the highest concentration of the tetrahedral components ,, , but could maintain their nanoscale sizes at the low concentration of 50 μM at room temperature, indicating that the peripheral substituents of the tetrahedral components did not affect the stability of the frameworks. Therefore, they could not only function as antidotes to neutralize the anticoagulation activity of residual heparins and alleviate the posttreatment phototoxicity of residual PDAs but also work well as nonequilibrium carriers, conducting in situ loading and the intracellular delivery of antitumor drugs and PDAs, ,,,, which has been ascribed to the so-called enhanced permeability and retention (EPR) effect . Apart from inclusion-based biomedical applications, dSOFs can also be conjugated with antitumor agents, forming new supramolecular prodrugs to attain enhanced efficacy .…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Previously we found that SOFs can in situ load anticancer agents and overcome the multidrug resistance of tumour cells to realize intracellular drug delivery and efficacy enhancement through the EPR effect. 32–35 Because the tetrahedral components can be readily functionalized at the ends of the appended aromatic units, 36 we conjectured that SOFs might be developed as albumin surrogates to conjugate AlDox or other small-molecule anticancer agents to attain increased efficacy through efficient conjugation, intracellular delivery and stimuli-responsive release. Here we describe the preparation of two SOF-based prodrugs by attaching AlDox to the interior of their regular pores through the thiol–maleimide conjugation approach.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Herein, we explore the sequestration of NMBAs by framework materials. Metal-organic frameworks (MOFs), [24][25][26] covalent-organic frameworks (COFs) 27,28 and supramolecularorganic frameworks (SOFs) [29][30][31] are important framework materials. To sequester NMBAs, we use a new type of frameworks, flexible organic frameworks (FOFs), which are biocompatible, stable and capable of encapsulating pharmaceutical or biological guests [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%